The Forefront for Novel Therapeutic Agents Based on the Pathophysiology of Lower Urinary Tract Dysfunction: Pathophysiology of Voiding Dysfunction and Pharmacological Therapy - Masayuki Takeda; Isao Araki; Tsutomu Mochizuki; Hiroshi Nakagomi; Hideki Kobayashi; Norifumi Sawada; Hidenori Zakohji (Elsevier, 2010)
Normal lower urinary tract function consists of voiding and storage. During voiding, the pontine micturition reflex center orders the sacral parasympathetic nucleus to increase parasympathetic activity, resulting in urinary bladder detrusor contraction via activation of post-synaptic muscarinic receptors (M2/3) and in the relaxation of both urethral and prostatic smooth muscle by nitric oxide (NO). In addition, the rhabdosphincter relaxes by inhibition of the pudendal nucleus at the sacral portion. During the storage phase, increase in sympathetic activity relaxes the urinary bladder via activation of post-synaptic β3-receptors and in the contraction of both urethral and prostatic smooth muscles via α1-adrenoceptor. Many factors influence voiding function, including lower urinary tract disorders (benign prostatic hyperplasia in males, urethral stricture) and neurological disorders (central and peripheral). Theories of pharmacotherapy for voiding dysfunction are 1) increase detrusor contractility and 2) decrease urethral resistance. The former includes agonists for muscarinic receptors and cholinesterase inhibitor; and the latter includes α1-adrenoceptor antagonists, NO donors, benzodiazepines, baclofen, dantrolene, and boturinum toxin. Keywords:: lower urinary tract symptoms (LUTS), voiding dysfunction, pharmacotherapy